Validation of perceived invalidation of emotion scale (PIES) in Iranian populations - Mehdi Rezaei; Zahra Paripishbar; Samaneh Khazaei (Discover Psychology)
Abstract Background The examination of the psychometric properties of the PIES in Eastern cultures has remained unexplored. The current study aims to explore the psychometric features of the PIES in Iranian populations. Methods A total of 2250 participants (clinical sample = 177, student samples = 1762, general population = 311) completed the following questionnaires: Perceived Invalidation of Emotion Scale (PIES), Childhood Trauma Questionnaire-Short form (CTQ-SF), Depression, Anxiety and Stress (DASS-2), and the Difficulties in Emotion Regulation Scale-16 (DERS-16). The psychometric qualities of the PIES were examined using construct, convergent, discriminant, incremental, and predictive validities together with internal consistency and test–retest reliability. Results The results of exploratory and confirmatory factor analysis revealed that the PIES had a unifactorial structure. Support was found for internal consistency as well as for test–retest reliability. In addition, the PIES scores significantly predicted emotional distress over time and had positive correlations with emotional dysregulation, childhood traumas, anxiety, stress, and depression. The PIES was also found to discriminate the clinical from nonclinical populations. Finally, PIES demonstrated adequate incremental validity. Conclusion Despite the limitations of the current study and the need for additional research, the findings indicate that the PIES with unifactorial structure is a reliable and valid scale among Iranian populations.